Meneladani Kesabaran dan Ketabahan Rasul Ulul âAzmi dalam Berdakwah: Studi Kisah-Kisah dalam Al-Qurâan - Amrie, M.Abduh (UIN Antasari Banjarmasin, 2012)
One of the basic substative content of the Quran is the the story of the past as a form of dakwah methods of the Quran to mankind. Among the story is about the Apostles of Ulul Azmi. They were included Noah, Moses, Abraham, Isa, and the Muhammad. They were all prophets and messengers who faced the strong challenges and opposition from their people, but thanks to their courage and patience they remained strong and continued to fight for the sake of upholding the Tawheed on this earth. Their character should be followed by every person who wants to take part in the field of dakwah and concentrate on calling people to the religion of Allah.